Community-based newborn hearing screening programme for early detection of permanent hearing loss in Iran: An eight-year cross-sectional study from 2005 to 2012. (March 2014) - Firoozbakht, Mohsen; Mahmoudian, Saeid; Alaeddini, Farshid; Esmaeilzadeh, Mansour; Rafiei, Minoo; Firouzbakht, Aryan; Rahimi, Farzad; Farhadi, Mohammad
Objectives: We here present the results of the first eight years of the newborn hearing screening programme in Iran, with a view to establishing the prevalence of hearing impairment among infants, and the efficacy of the programme. Methods: A total of 3, 350, 995 infants were screened using the series method of transient evoked otoacoustic emissions (TEOAEs)/automated auditory brainstem responses (AABRs), between 2005 and 2012. The infants were first tested for TEOAEs (three times). Based on the results of this test, the positive cases were referred to the next stage, where they were tested for AABRs. If they also tested positive on AABRs, they were referred to the diagnostic and rehabilitation stages. Results: Results of this study indicated an infant hearing impairment prevalence of 3 per 1000. Although this rate was as high as 5 per 1000 in the early years of the programme, it decreased to 2.6 per 1000 in the last year. The absolute referral rate was 14.5% in the first stage, which decreased to 0.9% and 0.2% in the second and the third stages, respectively. The follow-up rate was 70% in the first stage, which increased up to 73% and 85% in the second and the third stages, respectively. Conclusion: The study results suggest that the prevalence of hearing impairment in infants in Iran is comparable with that in developed and developing countries, and that the series TEOAEs/AABRs method used in the screening programme in Iran is efficient.